The effects of short video app–guided mindfulness meditation on rumination, self-compassion, psychological flexibility, and depression among individuals experiencing entrepreneurial failure - Tu, Ye-hui; Liu, Chao; Gao, Zheng-Hao; Chen, Hao (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of a short video app–guided mindfulness meditation intervention in improving psychological flexibility and self-compassion and reducing rumination and depressive symptoms among failed entrepreneurs.MethodsA randomized controlled trial was conducted with 100 recently failed entrepreneurs (aged 25–55), who were randomly assigned to either an intervention group (n = 50) or a waitlist control group (n = 50). Over five weeks, the intervention group completed daily 3-minute guided mindfulness meditation sessions via a secure mobile app. Psychological outcomes—including rumination, self-compassion, psychological flexibility, and depression—were assessed at pre- and post-intervention using validated instruments(Self-Compassion Scale – Short Form, SCS-SF), psychological flexibility (Acceptance and Action Questionnaire–II, AAQ-II). Data were analyzed using a two-step approach: a 2 (Group: Intervention vs. Control) × 2 (Time: Pre vs. Post) mixed-design MANOVA was first conducted to assess overall multivariate effects, followed by repeated measures ANOVAs for each outcome variable.ResultsSignificant group × time interaction effects were observed across all outcome variables. Compared to the control group, the intervention group showed significant reductions in rumination (F (1, 98) = 14.485, p <.001, η² = .073) and depression (F(1, 98) = 9.241, p = .003, η² = .045), as well as significant improvements in self-compassion (F(1, 98) = 11.764, p <.001, η² = .057) and psychological flexibility (F(1, 98) = 13.464, p <.001, η² = .064).ConclusionsThis study provides robust empirical support for the efficacy of mobile-guided mindfulness interventions in promoting mental health recovery among failed entrepreneurs. The findings highlight the potential of short video–based mindfulness practices as scalable, low-barrier tools to reduce cognitive vulnerability and emotional distress following entrepreneurial failure.Clinical trial registrationChinese Clinical Trial Registry (ChiCTR), identifier ChiCTR2500106524.